Non-destructive method of blood serum composition analysis in forensic science - Kovalchuk, Volodymyr; Krivda, Grihory; Zagorodniy, Viktor; Zagorodniy, Igor (Technium BioChemMed, 2024)
The article is devoted to consideration of non-destructive methods of blood serum composition analysis in forensics, problem solving and their improvement. At the current stage of creating materials and devices of a new generation, the task is not only to manage their properties, but also to effectively use them in various fields, in particular, in forensics. Analysis of the structural evolution of a heteroatomic liquid (in particular, blood) from the standpoint of theoretical and experimental approaches allows us to open new horizons in the practical plane, to determine the phenomenology of the process based on modern research methods. The authors of this work conducted a qualitative and quantitative analysis of experimental data related to the kinetics and mechanisms of structure formation of a multicomponent substance in the liquid state. It should be emphasized that the structural kinetics of a liquid such as blood serum, or blood itself, is a complex multistage process.